Grb2 Induces Cardiorenal Syndrome Type 3: Roles of IL-6, Cardiomyocyte Bioenergetics, and Akt/mTOR Pathway - Wang, Jin; Sun, Xuefeng; Wang, Xu; Cui, Shaoyuan; Liu, Ran; Liu, Jiaona; Fu, Bo; Gong, Ming; Wang, Conghui; Shi, Yushen; Chen, Qianqian; Cai, Guangyan; et al. (Frontiers in Cell and Developmental Biology, 2021)
Cardiorenal syndrome type-3 (CRS-3) is a damage to heart following acute kidney injury (AKI). Although many experiments have found that inflammation, oxidative stress, and cardiomyocyte death are involved in cardiomyocyte pathophysiological alterations during CRS-3, it lacks a non-bias analysis to figure out the primary mediator of cardiac dysfunction. Herein, proteomic analysis was operated in CRS-3 and growth factor receptor-bound protein 2 (Grb2) was identified as a regulator involving AKI-related myocardial damage. Increased Grb2 was associated with cardiac diastolic dysfunction and mitochondrial bioenergetics impairment; these pathological changes could be reversed through administration of Grb2 specific inhibitor during AKI. Molecular investigation illustrated that augmented Grb2 promoted cardiomyocytes mitochondrial metabolism disorder through inhibiting the Akt/mTOR signaling pathway. Besides, Mouse Inflammation Array Q1 further identified IL-6 as the upstream of stimulator of Grb2 upregulation after AKI. Exogenous administrator induced cardiomyocyte damage and mitochondrial bioenergetics impairment whereas this effect was nullified in cardiomyocytes pretreated with Grb2 inhibitor. Altogether, our results identify CRS-3 is caused by IL-6/Grb2 upregulations which contribute to cardiac dysfunction through inhibition of Akt/mTOR signaling pathway and induction of cardiomyocytes mitochondrial bioenergetics impairment. This finding provides a potential target for the clinical treatment of patients with CRS-3.